ANALISIS DAMPAK PADA ANAK BROKEN HOME TERHADAP MINAT BELAJAR SISWA KELAS V SD NEGERI NGLAMPIN 1 NGAMBON - Amma Azizah Munawaroh; Fachrur Rozie (LPPM Universitas Cipta Mandiri, 2024)
This research aims to analyze the impacts faced by children from broken home families in the elementary school (SD) environment. This study uses a qualitative method. The data collection techniques used were observation and interviews. Based on research results, broken home families can have an impact on children's behavior, emotions, academis and social adjustment. So that it affects their development and academic achievement. By understanding the impacts faced, it is hoped so that a workable solution can be developed help these children.